State-of-the-Art Review on Automotive Radars and Passive Radar Reflectors : Arctic Challenge research project - Händel, Chris; Konttaniemi, Heikki; Autioniemi, Matti (Lapin ammattikorkeakoulu, 2018)
Automation will enable safer, more green and efficient road transport in the upcoming decades. In order to exploit the full potential of automation, autonomous vehicles have to operate also in arctic environments, and in cold and icy conditions. This review is the first part of research project that aims at testing the feasibility of passive roadside radar reflectors for autonomous driving in snowy conditions. The content comprises of state-of-the-art revision of radar techniques, automotive radars and passive radar reflectors. This research is conducted by Lapland University of Applied Sciences and Roadscanners in Arctic Challenge research project. The Arctic Challenge research project is funded by the Finnish Transport Agency (FTA) and Finnish Transport Safety Agency (TraFi). The project is part of the Aurora intelligent road project of the Finnish Transport Agency and the NordicWay2 project funded by the Connecting Europe Facility of the European Union. The testing weeks of the research project will take place on the 10-km-long test stretch of the Aurora Vt21 (E8) intelligent road section in years 2017–2019. Furthermore, the project is part of the Traffic Lab cooperation. The contracting partners involved in the research project include Dynniq Finland Oy, Indagon Oy, Infotripla Oy, Lapland University of Applied Sciences Oy, Roadscanners Oy, Sensible 4 Oy and VTT Technical Research Centre of Finland Oy.